Endophilin B2 facilitates endosome maturation in response to growth factor stimulation, autophagy induction, and influenza A virus infection - Serfass, Jacob M. (J Biol Chem, 2017)
Endocytosis, and the subsequent trafficking of endosomes, requires dynamic physical alterations in membrane shape that are mediated in part by endophilin proteins. The endophilin B family of proteins contains an N-terminal Bin/amphiphysin/Rvs (N-BAR) domain that induces membrane curvature to regulate intracellular membrane dynamics. Whereas endophilin B1 (SH3GLB1/Bif-1) is known to be involved in a number of cellular processes, including apoptosis, autophagy, and endocytosis, the cellular function of endophilin B2 (SH3GLB2) is not well understood. In this study, we used genetic approaches that revealed that endophilin B2 is not required for embryonic development in vivo but that endophilin B2 deficiency impairs endosomal trafficking in vitro, as evidenced by suppressed endosome acidification, EGFR degradation, autophagic flux, and influenza A viral RNA nuclear entry and replication. Mechanistically, although the loss of endophilin B2 did not affect endocytic internalization and lysosomal function, endophilin B2 appeared to regulate the trafficking of endocytic vesicles and autophagosomes to late endosomes or lysosomes. Moreover, we also found that despite having an intracellular localization and tissue distribution similar to endophilin B1, endophilin B2 is dispensable for mitochondrial apoptosis. Taken together, our findings suggest that endophilin B2 positively regulates the endocytic pathway in response to growth factor signaling, autophagy induction, and viral entry.